Comparative genomic analyses reveal a vast, novel network of nucleotide-centric systems in biological conflicts, immunity and signaling. Issue 22 (20th November 2015) - Burroughs, A. Maxwell; Zhang, Dapeng; Schäffer, Daniel E.; Iyer, Lakshminarayan M.; Aravind, L.
Abstract: Cyclic di- and linear oligo-nucleotide signals activate defenses against invasive nucleic acids in animal immunity; however, their evolutionary antecedents are poorly understood. Using comparative genomics, sequence and structure analysis, we uncovered a vast network of systems defined by conserved prokaryotic gene-neighborhoods, which encode enzymes generating such nucleotides or alternatively processing them to yield potential signaling molecules. The nucleotide-generating enzymes include several clades of the DNA-polymerase β-like superfamily (including Vibrio cholerae DncV), a minimal version of the CRISPR polymerase and DisA-like cyclic-di-AMP synthetases. Nucleotide-binding/processing domains include TIR domains and members of a superfamily prototyped by Smf/DprA proteins and base (cytokinin)-releasing LOG enzymes. They are combined in conserved gene-neighborhoods with genes for a plethora of protein superfamilies, which we predict to function as nucleotide-sensors and effectors targeting nucleic acids, proteins or membranes (pore-forming agents). These systems are sometimes combined with other biological conflict-systems such as restriction-modification and CRISPR/Cas. Interestingly, several are coupled in mutually exclusive neighborhoods with either a prokaryotic ubiquitin-system or a HORMA domain-PCH2-like AAA+ ATPase dyad. The latter are potential precursors of equivalent proteins in eukaryotic chromosome dynamics. Further, components from these nucleotide-centric systems have been utilized in several other systems including a novel diversity-generating system with a reverse transcriptase. We also found the Smf/DprA/LOG domain from these systems to be recruited as a predicted nucleotide-binding domain in eukaryotic TRPM channels. These findings point to evolutionary and mechanistic links, which bring together CRISPR/Cas, animal interferon-induced immunity, and several other systems that combine nucleic-acid-sensing and nucleotide-dependent signaling.